PAPS: A Serverless Platform for Edge Computing Infrastructures - Baresi, Luciano; Quattrocchi, Giovanni (Frontiers in Sustainable Cities, 2021)
Edge computing infrastructures are often employed to run applications with low latency requirements. Users can exploits nodes that are close to their physical positions so that the delay of sending computations and data to the Cloud is mitigated. Since users frequently change their locations, and the resources available in the Edge are limited, the management of these infrastructures poses new, difficult challenges. This paper presents PAPS (Partitioning, Allocation, Placement, and Scaling), a framework for the efficient, automated and scalable management of large-scale Edge topologies. PAPS acts as a serveless platform for the Edge. Service providers can upload applications as compositions of lightweight and stateless functions along with latency constraints. At runtime, PAPS manages these applications by executing them in containers, it changes their placement in the Edge topology according to the geographical distribution of the workload, and efficiently allocates resources according to their needs. This paper also presents the architecture of a PAPS prototype built atop Kubernetes and OpenFaaS. The assessment shows both the feasibility of the approach and the ability of efficiently managing hundreds of serverless concurrent functions and of dealing with intense and unpredictable workload variations.